Regulatory T cell therapy for myeloperoxidase-specific anti-neutrophil cytoplasmic antibody associated vasculitis - Tay, Elean S. V.; Ting, Yi T.; Gan, Poh-Yi; Ooi, Joshua D. (Frontiers in Immunology, 2025)
Anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV) is a rare autoimmune disease characterized by the inflammation of small vessels. It is most commonly caused by ANCA targeting proteinase 3 (PR3) and myeloperoxidase (MPO) which are found in neutrophil lysosomes. The most common affected organs are respiratory tracts and kidneys, though other organs can be involved too. Although the cause of disease between PR3-AAV and MPO-AAV is similar, they vary in pathogenesis. Epigenetic and genetic factors may play a role in the disease development as certain population such as Chinese with HLA-DRB1*04:05 are more prevalent in MPO-AAV patient population. The prognosis for them is usually poor, often resulting in end-stage renal failure even with existing treatment. Current treatment for AAV relies heavily on corticosteroids which are toxic for long-term usage. Hence, there is a strong need to develop new, less toxic and targeted therapy for this disease. Regulatory T cell (Treg) therapy is a new type of therapy with the potential to specifically re-establish tolerance to the target autoantigen (MPO or PR3). This review will delve into the pathogeneses of AAV and discuss the potential of using genetically engineered Tregs to treat the cause of disease.